Application of Tissue Culture in Breeding for Biotic Stress Resistance - Abu, Mohammed (International Journal For Research In Agricultural And Food Science, 2021)
One of the problems facing agriculture today is related to the growing world population wich requires increase in food production while agricultural production is being challenged by biotic and a biotic stresses. Biotic stress includes various plant pathogens such as bacteria, fungi, viruses, nematodes, insects, and others whose infection arises from them frequently results in changes in plant physiology, the loss of biomass, early flowering, the decreased seed set, the accumulation of protective metabolites, and many other changes. One way to increase the quantity and quality of food is by reducing losses caused by insects, diseases and weeds by developing resistant crops or use of chemicals/ pesticides. Using chemical spray may have adverse effects on human health and the environment, including beneficial organisms and may lead to the development of chemical-resistant insects and weeds. Therefore, development of plants that continuously defend them-selves against attacks from bacteria, viruses, fungi, invertebrates, and even other plants is found to be important. The long-term goal of plant breeders is to improve crops for biotic stress tolerance. This can be achieved by the using modern breeding technique. Among them the use of Plant genetic engineering and tissue culture has made possible.